Estimación de la estatura usando el método de Carrea en un grupo de individuos colombianos (2022)
Introduction: The estimation of height is part of the quatrain in the process of human identification. It is a parameter that can be set with the long bones; however, when these are not found, other structures must be used, such as the teeth. Objective: To determine the accuracy of Carrea's formula for estimating height in a group of individuals, and to explore the correlations of the variables used in Carrea's formula with the height of Colombian adult individuals.